The CDM low-hanging fruits problem under ex-ante and ex-post baselines. (12th September 2019) - Labidi, Etidel; Abdessalem, Tahar
The Kyoto Protocol set up the so-called 'clean development mechanism' (CDM) to help industrialised countries to meet their emission targets. This is made possible through allowing the use of emission credits generated by emission reduction projects undertaken in developing countries. Two important issues surround the implementation of CDM: the 'low-hanging fruits' (LHF) and the alternative baseline types. To examine the interactions between these issues, we have modelled the behaviour of a monopolistic firm with the possibility of participating in CDM projects. Under an ex-ante baseline, the CDM project increases marginal cost during the first period. Consequently, the output produced by the firm decreases and emissions are reduced. In our study, the LHF problem occurs if the firm does not take into account the future emission reduction or limitation commitments and the irreversibility aspect of abatement measures. Therefore, the increase in the myopic marginal cost is higher than predicted. Under an ex-post baseline, the CDM project decreases marginal cost, increasing the firm's output level. The low-hanging fruits problem takes place if the marginal cost in the myopic behaviour decreases more than predicted. In our study, the extent of the LHF problem increases under a permits' endowment effect but decreases under the irreversibility effect.